2012
DOI: 10.4161/nucl.18927
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the lamin protein family

Abstract: Lamins are the major components of the nuclear lamina, a filamentous layer found at the interphase between chromatin and the inner nuclear membrane. The lamina supports the nuclear envelope and provides anchorage sites for chromatin. Lamins and their associated proteins are required for most nuclear activities, mitosis, and for linking the nucleoskeleton to the network of cytoskeletal filaments. Mutations in lamins and their associated proteins give rise to a wide range of diseases, collectively called laminop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 133 publications
0
68
0
Order By: Relevance
“…9 Invertebrates have in general only one B-type lamin whereas A-type lamins only exist in vertebrates, indicating that lamin A is an evolutionary more recent protein. 10 The cytoplasmic IFs found in lower organisms are more closely related to lamins than to cytoplasmic IFs in higher organisms. 11 This indicates that a B-type lamin was the first IF to evolve and that this founder IF gradually gave rise to cytoplasmic IFs and later to A-type lamins.…”
Section: Lamins Are Intermediate Filament Proteinsmentioning
confidence: 99%
“…9 Invertebrates have in general only one B-type lamin whereas A-type lamins only exist in vertebrates, indicating that lamin A is an evolutionary more recent protein. 10 The cytoplasmic IFs found in lower organisms are more closely related to lamins than to cytoplasmic IFs in higher organisms. 11 This indicates that a B-type lamin was the first IF to evolve and that this founder IF gradually gave rise to cytoplasmic IFs and later to A-type lamins.…”
Section: Lamins Are Intermediate Filament Proteinsmentioning
confidence: 99%
“…Thus, the SC components are not the first case in which Drosophila and C. elegans hold a rather exceptional role. Evolutionary analysis of the lamin gene(s) in Metazoa for example revealed that just Drosophila and C. elegans exhibit an unusual gene organization most likely due to a strong genetic drift (Peter and Stick 2012).…”
Section: The Dynamic Evolution Of the Scmentioning
confidence: 99%
“…An explanation for the strong differences in SC protein sequences between these two species and the other metazoans described here may be the evolutionary drift of ecdysozoans. This view is not without precedent in the literature as it has been already proposed for other structural proteins as is the case of lamins, the major components of the nuclear lamina (25,26), as well as for ribosomal DNA (27). In support of this, our bioinformatic analysis with C(3)G [the TF protein of D. melanogaster (28)] and SYP1-4 [the TF proteins of C. elegans (29)] in each case revealed only protein sequences from the respective genus, underscoring the proposal of a great sequence diversity and a rapid evolution within this clade (27).…”
mentioning
confidence: 94%